Fatty acid composition of total lipids in liver of carp (Cyprinus carpio L.) under artificial hibernation - Sysolyatin, S.V.; Khyzhnyak, S.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
The composition and the quantitative content of fatty acids of total lipids in liver of scaly carp under artificial hibernation are studied. The method of gas chromatography identified 28 fatty acids, the quantitative content of which changes when fish are in the state of artificial hibernation. It has been established that a redistribution in the quantitative ratio of fatty acids leads to a decrease of the total content of saturated fatty acids and an increase of the content of unsaturated ones, mainly due to polyunsaturated acids.